A Practical Approach to 6H-Indol-6-ones Enables the Formal Synthesis of γ-Lycorane - Chen, Yang; Hu, Xin-Ting; Xie, Xiao-Yan; Li, Dashan; Zheng, Chun-Xia; Zhang, You-Xi; Wang, Wen-Jing; Zhan, Rui; Shao, Li-Dong (Synthesis, 2022)
We represented herein a two-step synthesis of 1-methyl-6H-indol-6-one which is an N-containing 6/5 fused bicyclic building blocks in Amaryllidaceae alkaloids. The key step featured is a ‘one-pot’ ozonolysis/reductive amination/cyclization of allylated cyclohexa-1,3-dione to give bicyclic compounds. Moreover, the formal total synthesis of natural product γ-lycorane could be achieved through a photo-promoted cyclization/oxidation cascade reaction from the resulting bicyclic intermediate.
Keywords: 1-methyl-6H-indol-6-one; two-step synthesis; one-pot; Amaryllidaceae alkaloids; γ-lycorane